Back to the classics: editing the Emanuel Saxe legacy for modern accounting. (2015) - Tinker, Tony; Sy, Aida
This article quotes the work of Emanuel Saxe, which says that recent emphasis upon the place and role of the behavioural sciences in education for business administration (a term which also includes industrial management) bespeaks a change from the purely vocational aspects of such training. This change is not some intellectual brainstorm of university presidents and deans but rather reflects underlying changes in American life and in the type of society which has been evolving in the last 25 years. Three stages of higher education for business administration are identified and discussed: the stage of rugged individualism; the stage of corporate capitalism; the stage of social capitalism.